The Efficacy of Various Conditioning Methods in Restoring the Color of White Spot Lesions Through Resin Infiltration: Er,Cr:YSGG laser for resin infiltration - Boruziniat, Alireza; Ahrari, Farzaneh; Shafaee, Hooman; Faravani, Farnoosh; Rangrazi, Abdolrasoul; Akbari Kamrani, Farhad; Fallahrastegar, Amir (Journal of Lasers in Medical Sciences, 2025)
Introduction: This study aimed to assess the effects of supplemental conditioning methods, including extended etching time, Er,Cr:YSGG laser radiation, and sandblasting, on enhancing the recovery of white spot lesions (WSLs) through resin infiltration. Methods: Seventy premolars were subjected to a cariogenic solution to induce WSLs. Subsequently, the teeth were divided into 5 groups of 14, based on the enamel conditioning protocol applied, as follows: Group 1: Icon-Etch (Control), Group 2: Double Icon-Etch, Group 3: Sandblasting+Icon-Etch, Group 4: Er,Cr:YSGG laser+Icon-Etch, and Group 5: IconEtch+Er,Cr:YSGG laser+Icon-Etch. The Er,Cr:YSGG laser (2780 nm) was applied at 0.75 W and 20 Hz. Tooth color was measured initially (T0), after WSL induction (T1), and following resin infiltration (T2). Color changes between treatment stages were compared among the groups. Results: One-way analysis of variance (ANOVA) displayed no significant differences in ΔET0-T1 or ΔET1-T2 between the groups (P>0.05). However, a significant difference was found between the groups in the color change from baseline to post-resin infiltration (ΔET0-T2) (P=0.004). The ΔET0-T2 was significantly lower in groups 4 and 5 compared to the control group and group 3. Group 2 did not demonstrate a significant difference from the other groups (P>0.05). Conclusion: The combination of laser etching and acid etching was effective in enhancing the recovery of WSLs through resin infiltration. The ΔET0-T2 in groups subjected to laser plus acid etching fell below the critical threshold of 3.7 units, indicating that the post-treatment tooth color was not clinically distinguishable from the original tooth color.